1996
DOI: 10.1161/01.hyp.27.6.1259
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Neutral Endopeptidase Inhibition in Rats With Aortocaval Shunt

Abstract: In heart failure, sodium and water retention develop despite elevated plasma levels of atrial natriuretic peptide. Atrial natriuretic peptide is degraded in part by a neutral endopeptidase. Whether neutral endopeptidase inhibition improves sodium and water excretion in heart failure is unknown. We determined the effect of neutral endopeptidase inhibition on plasma levels of atrial natriuretic peptide and the renal response to acute volume expansion in rats with aortocaval shunts and in sham-operated controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…We and others (8,24,28) demonstrated that the inhibition of the angiotensin-converting enzyme or of the angiotensin II type 1 receptor (AT 1receptor) improved the baroreflex control. In the model of chronic volume overload, a moderate activation of the renin-angiotensin-aldosterone system occurs (41), and it is conceivable that this mechanism might contrib-ute to the early depression of baroreflex control of sympathetic nerve activity, which we report in this study. Thus, an influence of humoral activation of the renin-angiotensin-aldosterone system and of ANP might contribute to the impaired baroreflex control of sympathetic nerve activity.…”
Section: H2583mentioning
confidence: 49%
See 1 more Smart Citation
“…We and others (8,24,28) demonstrated that the inhibition of the angiotensin-converting enzyme or of the angiotensin II type 1 receptor (AT 1receptor) improved the baroreflex control. In the model of chronic volume overload, a moderate activation of the renin-angiotensin-aldosterone system occurs (41), and it is conceivable that this mechanism might contrib-ute to the early depression of baroreflex control of sympathetic nerve activity, which we report in this study. Thus, an influence of humoral activation of the renin-angiotensin-aldosterone system and of ANP might contribute to the impaired baroreflex control of sympathetic nerve activity.…”
Section: H2583mentioning
confidence: 49%
“…Several mechanisms could have contributed to the early alterations of baroreflex control in this model. The aortocaval shunt model is characterized by an activated ANP system (40,41). We measured a threefold increase of plasma concentrations of ANP in aorto-…”
Section: H2582mentioning
confidence: 99%
“…However, it is becoming increasingly clear that the notion that NEP inhibitors act merely by increasing the blood levels of ANP, ET‐1, and other vasoactive substances is an oversimplification. Rather, recent studies using sinorphan or thiorphan have convincingly demonstrated intrarenal effects, predominantly in the tubules where NEP activity is high, independent of the degree of plasma ANP augmentation which is inconsistent (Trapani et al ., 1989; Willenbrock et al ., 1996; Solter et al ., 2000). Therefore, we remain unconcerned about the insignificant elevations of ET‐1 and ANP in our cirrhotic rats; the significant increase in natriuresis in this group confirms, in our view, the efficacy of the thiorphan dose despite the inability to raise these vasoactive substance levels in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NEP potentiates the vasodilator, diuretic, and natriuretic effects of these two peptidergic systems and has beneficial effects in animal models of heart failure (Seymour et al 1993;Rademaker et al 1996;Willenbrock et al 1996). It may thus be postulated that the simultaneous inhibition of ACE and NEP may be superior to ACE inhibition alone post-MI.…”
Section: Introductionmentioning
confidence: 99%